Planning beyond Mass Incarceration. (June 2020) - Simpson, Sheryl-Ann; Steil, Justin; Mehta, Aditi
The policing and penal systems play an oversized role in shaping the built environment and budgets of cities, alongside the lives of urban residents. Law enforcement systems are also deeply inequitable with poor residents, and communities of color disproportionately harmed by the violences of the system. Planning's contribution to the creation of durable spatial stratification in the built environment implicates planning in the class and race disparities in law enforcement systems. Planning research and theory has also supported this inequity by largely neglecting the relationships between policing and penal systems and planning. The articles in this volume address this neglect and employ a wide variety of core theories, methods, and methodologies from planning to engage with the relationships between planning and law enforcement. The articles are connected through attention to racial justice including analyzing moments where planning supported and produced injustice, and identifying opportunities to support greater equity, decarceration and even abolition where planning practice, education and research support the creation of systems of safety and care beyond mass incarceration.